Beliefs about psychotherapy among adults in La Araucanía, Chile - Natalia Salinas-Oñate; María José Baeza-Rivera; David Mellor; Ximena Ossa (Universidad de Chile, 2019)
Cultural factors relevant to psychotherapy, although highly relevant, have been poorly studied in the local context, with little clarity regarding the socially shared meanings about this kind of treatment. The aim of this study was to identify beliefs about psychotherapy among adults from La Araucanía region, Chile. Through a bottom up cultural research approach, 32 semi-structured interviews were conducted and examined using thematic analysis. Partici-pants held mostly positive beliefs about psychotherapy itself and its results. However, understandings that could hinder adherence to psychotherapy were identified, as well as negative emotions associated with attending it. Addi-tionally, participants displayed negative beliefs about the psychotherapy delivered in the public health system. These results provide a characterization of beliefs about psychotherapy among adults, and could serve as an input to understand psychotherapy adherence in this particular context.